2008
DOI: 10.1074/jbc.m704147200
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Mesenchymal Stem Cell Osteogenic Differentiation by Glucocorticoid-induced Leucine Zipper (GILZ)

Abstract: Mesenchymal stem cells (MSCs) can differentiate into multiple cell lineages, including osteoblasts and adipocytes. We reported previously that glucocorticoid-induced leucine zipper (GILZ) inhibits peroxisome proliferator-activated receptor ␥-2 (Ppar␥2) expression and blocks adipocyte differentiation. Here we show that overexpression of GILZ in mouse MSCs, but not MC3T3-E1 osteoblasts, increases alkaline phosphatase activity and enhances mineralized bone nodule formation, whereas knockdown of Gilz reduces MSC o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
133
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 130 publications
(140 citation statements)
references
References 46 publications
(15 reference statements)
6
133
0
1
Order By: Relevance
“…Previous studies showed that the shorter isoform GILZ can inhibit T cell activation/proliferation (22, 24, 26, 44 -46). GILZ has also been shown to control proliferation and differentiation in other cell types including adipocytes, osteoblasts, and myoblasts (28,47,48). Conservation of most of the GILZ functional domains in L-GILZ isoform suggests that L-GILZ can act as suppressor of cell growth and differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that the shorter isoform GILZ can inhibit T cell activation/proliferation (22, 24, 26, 44 -46). GILZ has also been shown to control proliferation and differentiation in other cell types including adipocytes, osteoblasts, and myoblasts (28,47,48). Conservation of most of the GILZ functional domains in L-GILZ isoform suggests that L-GILZ can act as suppressor of cell growth and differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…To further study this problem, a retrovirus-mediated GILZ overexpression system was established in bone marrow MSCs/osteoprogenitor cells. Studies carried out in this system showed that GILZ has potent pro-osteogenic activity as demonstrated by significantly increased alkaline phosphatase activity, enhanced mineralized bone nodule formation, and the expression of osteoblast-associated genes such as Runx2, type I collagen, alkaline phosphatase, and osteocalcin [100]. Furthermore, our recent studies have shown that overexpression of GILZ can antagonize the inhibitory effect of TNF- on MSC osteogenic differentiation [101].…”
Section: Gilz Mediates the Anabolic Effect Of Glucocorticoidsmentioning
confidence: 99%
“…BMSCs derived from 18-month-old mice were subjected to retroviral-mediated transduction with DU3-GFP plasmid DNA, constructed in the replication defective DU3nlsLacZ vector by inserting the full-length coding region of Gfp cDNA. 29 BMSCs were then retransplanted in tibiae of 2-month-old C57BL/6J mice and their osteogenic potential was confirmed in vivo (unpublished data). After 4 weeks, animals were euthanized, the marrow cells harvested, and seeded at low density for clonal selection.…”
Section: Isolation and Culture Of Bmscsmentioning
confidence: 99%
“…The isolation process, negative immunodepletion (CD11b, CD45R/B220, CD11c, plasmacytoid dendritic cell antigen-1 [PDCA-1]), positive immunoselection (stem cell antigen-1 [Sca-1]), and retroviral infection (GFP) have been described previously. 28,29 First, six mice per age group were euthanized by CO 2 overdose followed by thoracotomy. The femora and tibiae were dissected free of soft tissues and kept in cold PBS on ice.…”
Section: Isolation and Culture Of Bmscsmentioning
confidence: 99%